BEST4U.COM: A CREATIVE PLATFORM FOR SECONDHAND ITEMS TRANSACTION - Liu, Yufei; Anwarul , Karim; Hassan, Rakibul; Huda, Najmul; Riyas, Manaaz; Mahri, Nurhafizah (Journal of Information Systems and Digital Technologies, 2022)
This paper introduces a conceptual business model for a web and mobile application-based online platform called “Best4u.com”. This platform enables people to buy and sell second-hand products. “Best4u.com” aims to accomplish one of the Sustainable Development Goal 12, to ensure sustainable consumption and production patterns. The business model for this app is developed by the design thinking method, which helps to understand the crucial problems, possible solutions, validation of customers' segments, and suggestions for conceptual solutions. The other tools used are Business Model Canvas (BMC), Value Proposition Canvas (VPC), Environment Map (EM). A survey with the initial potential customers has been conducted to validate the initial Business Model Canvas and Value Proposition Canvas. The majority of our respondents are comfortable with internet shopping, and they use it to buy books, gadgets, and other items. The finding of the survey revealed that most individuals aren't interested in doing online secondhand buying because there aren't many effective business platforms available. They are, nevertheless, willing to buy their essential used things online if several important issues, such as delayed delivery, fraudulent products, and transportation costs, are addressed. Finally, this paper provides a validated conceptual business model of an online second-hand shopping platform/apps, which is called “Best4u.com”, with the goal of making online second-hand shopping easier.